Clicking molecular hooks on silica nanoparticles to immobilize catalytically important metal complexes: the case of gold catalyst immobilization - Ganai, Anal Kumar; Bhardwaj, Rima; Hotha, Srinivas; Sen Gupta, Sayam; Bhagavatula L. V. Prasad (New Journal of Chemistry, 2010)
Gold mediated reactions have emerged as one of the best choices for affecting a variety of chemical transformations with a wide range of functional group tolerance. Application of such transformations to industrial processes necessitates immobilization of the Au ions into a matrix for easy separation of the catalyst after reaction. We report the synthesis and characterization of silica nanoparticles in which Au(III) has been immobilized through a 1,2,3-triazole linkage using an alkynalated picolinic acid exploiting ``click chemistry''. The Au( III) immobilized silica nanoparticle has been thoroughly characterized using FT-IR, C-13 CP MAS NMR and XPS. The utility of these particles as an easily separable catalyst for the Hashmi phenol synthesis is also reported.

Rottlerin derivatives and other compounds from mallotus philippinensis fruits and their potential antimycobactrial activity - Bhardwaj, Rima; Chinchansure, Ashish A.; Kulkarni, Roshan R.; Arkile, Manisha A.; Sarkar, Dhiman; Joshi, Swati P. (Planta Medica Letters, 2015)
The methanolic extract of the fruits of Mallotus philippinensis afforded 13 compounds, 7,11-diketo-lanost-3-ol (1, as acetate), lanosta-8-ene-3β-ol (2, as acetate), pregnenolone (3, as acetate), trans-chalcone (4), kamalachalcone E (5), oleanolic acid (6), gallic acid (7), kaempferol (8), myricetin (9), 1-(5,7-dihydroxy-2,2,6-trimethyl-2 H-1-benzopyran-8-yl)-3-phenyl-2-propen-1-one (10), 4′-hydroxyisorottlerin (11), rottlerin (12), and shikimic acid (13). Compound 1 was isolated as a new natural product and its structure was elucidated by 1D and 2D nuclear magnetic resonance analyses including heteronuclear single quantum correlation, heteronuclear multiple-bond correlation, correlation spectroscopy, and nuclear Overhauser effect spectroscopy experiments. All of the isolated compounds were evaluated for their antimycobacterium activity against Mycobacterium tuberculosis H37Ra. Compounds 11 and 12 exhibited promising inhibitory activity with IC50 values of 0.89 ± 0.33 µg/mL (MIC 2.06 ± 0.41 µg/mL) and 7.59 ± 0.42 µg/mL (MIC 11.56 ± 0.35 µg/mL), respectively.